The importance of interaction between MicroRNAs and gut microbiota in several pathways. (July 2020) - Behrouzi, Ava; Ashrafian, Fatemeh; Mazaheri, Hoora; Lari, Arezou; Nouri, Matineh; Riazi Rad, Farhad; Hoseini Tavassol, Zahra; Siadat, Seyed Davar
Abstract: The human gut harbors diverse microbes that play a fundamental role in the well-being of their host. Microbiota disruption affects the immune function, metabolism, and causes several diseases. Therefore, understanding how the microbiome is adjusted, and identifying methods for manipulating it is critical. Studies have found that there is an inverse association between MicroRNAs (miRNAs) abundance and microbe abundance. miRNAs are known to be engaged in post-transcription regulation of cell-autonomous gene expression. Recently, they have gained great attention for their proposed roles in cell-to-cell communication, and as biomarkers for human disease. Here, we review recent studies on the role of miRNAs as a component of outer membrane vesicles (OMVs) in the composition of gut microbiota and their significance in the human situation of health and diseases and discuss their effect on inflammatory responses and dysbiosis. Further, we explain how probiotics exert influence on the expression of miRNAs. Highlights: The human gut harbors diverse microbes that play a fundamental role in the well-being of their host. Microbiota disruption affects the immune function, metabolism, and causes several diseases. Studies have found that there is an inverse association between MicroRNAs (miRNAs) abundance and microbe abundance.